Shortcrowna, a new genus of Evacanthinae (Hemiptera: Cicadellidae) from China - Li, Yu-Jian; Li, Zi-Zhong (Zootaxa, 2014)
The paper deals with a new leafhopper genus of Evacanthinae, Shortcrowna gen. nov., and four species of the genus, including three new combinations and one new species, Shortcrowna biguttata (Li & Wang, 2002) comb. nov., Shortcrowna flavocapitata (Kato, 1933) comb. nov., Shortcrowna nigrimargina (Li & Wang, 2002) comb. nov., Shortcrowna leishanensis sp. nov.. The differences between the new genus and the closely related genus Bundera Distant are discussed. A key to distinguish all species of the genus is given, and illustrations of genitalia are provided. The type specimens of new species are deposited in the Institute of Entomology, Guizhou University (GUGC).